Assessing seasonal climate variability impact on the malaria patient’s cases in the north of Côte d'Ivoire - SILUE, Siélé; Dago, Dougba Noel; Kouassi, Adjon Anderson; Dajuma, Alima; Doumbia, Madina; Touré, N’Datchoh Evelyne; Kéita, Sékou (European Journal of Applied Sciences, 2021)
In recent years, the impact of climate change on human health has attracted considerable attention including their effects on malaria, which have been of particular interest due to its disease burden and transmission sensitivity to climatic conditions. The main objective of the study is to examine the relationship between intra-annual climate variability and malaria transmission in the north of Côte d’Ivoire. The monthly incidence of malaria in Korhogo 1 health district was treated as a dependent variable, and meteorological variables were independent variables. Our results highlighted that malaria is influenced by all three climatic variables (rainfall, temperature and relative humidity). The highest effect of temperature, relative humidity, and rainfall on malaria cases is observed in the months of June, July, August, September, October and November respectively. The monthly rainfall and the monthly mean relative humidity were highly correlated to monthly incidence of malaria in population under-five years old. Meanwhile, the monthly mean temperature was highly correlated to malaria incidence of pregnant women over 15 years old and to monthly incidence of malaria in under-five. Moreover, combining monthly rainfall and monthly mean temperature, monthly rainfall and monthly mean relative humidity and monthly mean temperature and relative humidity were highly correlated to malaria incidence in patients influenced by the rainy season exclusively. The combination between monthly rainfall and monthly mean relative humidity was closely correlated to malaria incidence in malaria patient influencedby rainy and/or dry season.